Post Treatment Complication of Enteric Fever: A Rare Presentation - Paul, Nibedita; Islam, Md Rafiqul; Nusrat, Nadia; Rahman, Farhana; Hasan, Mahamudul (Delta Medical College Journal, 2016)
Background: Enteric fever is one of the common infectious diseases worldwide. Ceftriaxone is the most commonly used sensitive antibiotic for enteric fever. Biliary sludge is an important complication of ceftriaxone. Biliary sludge refers to a viscous mixture of small particles derived from bile. These sediments consist of cholesterol crystals, calcium salts, calcium bilirubinate, mucin, and other materials. For patients without symptoms, no treatment is recommended. If patients become symptomatic and/or develop complications, cholecystectomy is indicated. This is case report of a 9 year old boy diagnosed as a case of enteric fever and treated with appropriate dose of ceftriaxone for 8 days. On the day of discharge, at night the boy developed severe abdominal pain. They took surgical consultation; ultrasonography of whole abdomen was done which revealed multiple calculi in gall bladder. Symptomatic treatment was planned followed by surgical removal of biliary calculi. After 20 days they took surgical consultation again. Surgeon was ready to perform surgery. The worried mother requested for repeat USG of whole abdomen and this time finding was normal. We must be aware about side effects of ceftriaxone. Patients should be followed up after completion of treatmentand as biliary sludge is often self-limiting and surgery is not required for all cases. Delta Med Col J. Jul 2016 4(2): 97-100